PEMBUATAN PROTOTIPE KONTROL REL SLIDER KAMERA OTOMATIS MENGGUNAKAN MIKROKONTROLER - Mina Ismu Rahayu; Adis Sonjaya; Agus Soepriadi (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2015)
The camera slider rail is one of the supporting tools in video capture in the broadcast world that functions as a camera movement trajectory. The advantage of using this tool is that the video results obtained will be more dramatic. In order to move more consistently, it is necessary to make a tool that can adjust the movement of the slider rail.In this research, a device that can regulate the movement of the camera slider rail has been built, with the ability to adjust the speed of the slider rail movement consistently. Besides, this tool can adjust the direction of motion of the slider rail and can stop automatically if there are certain circumstances. This tool is named Camera slider rail control.The design of the tool uses Arduino Uno hardware as a microcontroller, while for software uses ArduinoIDE as a program code compiler.